Enhanced unified power quality conditioner control mechanism for power quality improvement / Kamrul Hasan - Hasan, Kamrul (2023)
Electrical power distribution quality has been significantly impacted by the widespread use of power electronic devices. Researchers have developed many dynamic and flexible solutions. Power electronics technology and fast-processing controllers have helped to introduce modern Unified Power Quality Conditioners (UPQC). UPQC is a recent Active Power Filter (APF) method for grid voltage and current-related power quality concerns. Four primary issues were discovered in this study demanding subsequent research. First, UPQCs have major inherent synchronization concerns that cannot be overcome by the conventional d-q control-based Phase-locked Loop (PLL) techniques. Nonlinear power electronic loads in the system cause power quality issues in the grid voltage, which adversely affect the performance of d-q-PLL. Second, the conventional reference current generation techniques for UPQC for solving current related power quality issues still have limitations including computational complexity, average filtration ability, and slow dynamic response. Third, the conventional reference voltage generation techniques for UPQC for solving voltage-related power quality issues are unable to reduce the system complexity because of dependency on conventional d-q-PLL and proportional-integral (PI) controllers. PI controller design needs an accurate linear mathematical model, which is difficult to develop in nonlinear and time-varying systems, making tuning for optimum gain values time-consuming. Finally, sensitive loads demand continuous power with finer power quality, yet grid voltage fluctuation, long interruptions are hindering their operation. Thus, this study focuses on three major control mechanisms that can improve the dynamic and mitigating operations of the UPQC and integrate energy storage systems to support sensitive loads. First, this work improves the d-q-PLL structure and proposes a Savitzky Golay Filter (SGF)-based PLL to solve UPQC's power quality-related synchronization issues. Next, this study enhances the conventional d-q technique and proposes an SGF-based reference current generation technique for UPQC with a simple structure, higher filtration ability, and faster dynamic response characteristics to improve UPQC performance and reduce grid current Total Harmonic Distortion (THD). Furthermore, Self-Regulated Phase estimator (SRPE)-based reference voltage generation method for UPQC is proposed that can simplify the control structure while improving dynamic responsiveness. Finally, a Photovoltaic (PV) and battery-integrated UPQC system is developed to increase its performance under poor grid conditions and support sensitive loads.